HUBUNGAN STATUS PEKERJAAN DAN PENGETAHUAN IBU DENGAN PEMBERIAN ASI ESKLUSIF DI KELURAHAN TANAH ENAM RATUS KECAMATAN MEDAN MARELAN TAHUN 2021 - Mastiur Julianti B (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2021)
Health development indicators can be seen from the increase in health status. One of the indicators of health status is the Infant Mortality Rate (IMR). The Infant Mortality Rate (IMR) in 2012 is still high, namely 32 per 1,000 live births, while the 2015 Millennium Development Goals (MDGs) target for IMR is 23 per 1,000 live births (SDKI, 2012). The United Nations Children's Fund (UNICEF) and the World Health Organization (WHO) pay attention to children who are breastfed only with breast milk (ASI) for a minimum of six months or what is known as exclusive breastfeeding in order to reduce infant morbidity and mortality (Kemenkes RI, 2014). The study aims to see the relationship between work status and maternal knowledge by providing exclusive breastfeeding in the working area of ​​Tanah Enam Ratus Village Medan Marelan Sub District in 2021. The sampling technique in this study was purposive sampling. The population in this study were all mothers who had babies> 6-24 months in Tanah Enam Ratus Village Medan Marelan Sub District as many as 70 people and the sample used total sampling. Data analysis using chi square test. The results of the chi square test showed that the results of the study showed that there was a relationship between job status (p = 0.00) and knowledge (p = 0.000) with offering exclusive breastfeeding. It is hoped that pregnant women can take the time to participate in the counseling organized by health workers at the Tanah Enam Ratus Village Medan Marelan Sub District about the importance of presenting Exclusive breastfeeding.